(untitled) (JURNAL KEPERAWATAN, 2014)
Abstract: Dengue fever is a public health problem in Indonesia and still being up to date problem. Based on a survey of PHC Gogagoman health center that Mogolaing villages are with Dengue Fever cases with the highest number of 24 cases. Perpose: This study aims to determine the relation of knowledge and family attitude with the Prevention of Dengue hemorrhagic fever (DHF) in the Mogolaing district. Research Methods: This study was conducted with a cross-sectional method, the selection of samples with purposive sampling with a sample of 100 families. Research Outcome: Analysis of the data using statistical test Chi Square with a limit of significance Î± = 0.05. Based on test results obtained probability value for the relation with family knowledge with dengue fever prevention of 0.000 (p> 0.05), while for the relation of family attitude with dengue prevention is 0.002 (P <0.05). Conclusion: The conclusion of this study is There is a Relations of Knowledge and Family Attitudes with dengue fever prevention in Mogolaing district. It is Suggested to health officials to improve the prevention of dengue fever with counseling to families in order to continue routine mosquito nets eradication. Suggestion: It is suggested to the family in Mogolaing to improve knowledge, attitude and active role in the prevention of dengue fever. Keywords: Knowledge, Attitude, Prevention of Dengue Fever Dengue Abstrak: Demam Berdarah Dengue merupakan salah satu masalah kesehatan masyarakat di Indonesia dan masih menjadi masalah kesehatan yang up to date. Berdasarkan survei dari Puskesmas Gogagoman didapatkan bahwa kelurahan Mogolaing merupakan kelurahan dengan kasus Demam Dengue tertinggi dengan jumlah 24 kasus. Tujuan untuk mengetahui Hubungan Pengetahuan dan Sikap keluarga dengan Pencegahan Demam berdarah dengue (DBD) di kelurahan Mogolaing. Metode Penelitian Penelitian ini dilaksanakan dengan metode cross sectional, pemilihan sampel dengan perpposive sampling dengan jumlah sampel 100 keluarga. Analisa data mengunakan uji statistik chi Square dengan batas kemaknaan Î± = 0,05. Hasil Penelitian: Berdasarkan Hasil uji didapatkan nilai probabilitas untuk hubungan pengetahuan keluarga dengan pencegahan demam berdarah dengue sebesar 0,000 (p>0,05), sedangkan untuk hubungan sikap keluarga dengan pencegahan demam berdarah dengue sebesar 0,002 (p<0.05). Kesimpulan: Ada Hubungan Pengetahuan dan Sikap keluarga dengan Pencegaha demam berdarah dengue di kelurahan Mogolaing. Disarankan kepada petugas-petugas kesehatan untuk lebih meningkatkan pencegahan demam berdarah dengue dengan penyuluhan kepada keluarga-keluarga agar tetap melaksanakan pemberantasan sarang nyamuk secara rutin. Saran: kepada keluarga-kelarga di kelurahan Mogolaing untuk meningkatkan Pengetahuan, sikap dan peran aktif dalam pencegahan demam berdarah. Kata kunci : Pengetahuan, Sikap, Pencegahan Demam Berdarah dengue